In-Service EFL teachers' engagement in reflexive practice via video enhanced observation. Issue 3 (4th May 2022) - Aslan, Ayça; Erten, İsmail Hakkı and Dikilitaş, Kenan
ABSTRACT: Building upon the interrelationship between learning and changing, this study investigates how cyclical engagement in reflexive practice influences the teachers' professional development. We implemented our video-enhanced 'Reflexive Practice Triplication Model' which we developed in our specific context. We conducted the research with 8 secondary school teachers of English at a private K12 school in Ankara, Turkey. Drawing on multiple sources of data, we used a triangulation technique to reveal the qualitative and quantitative impact of reflexive practice. The findings showed that collaborative engagement in reflexive practice contributed substantially to EFL teachers' professional development traceable in the changes in beliefs on reflexivity, attitudes towards collaboration, contextual and pedagogical knowledge. The study provides implications as to how reflexive practice can be used in local contexts where specific needs are to be considered.